TERAPI TOKEN EKONOMI UNTUK MENGUBAH PERILAKU LEKAT DI SEKOLAH - Hasanah, Nur (HUMANITAS (Jurnal Psikologi Indonesia), 2013)
AbstractThis research focused on attachment behavior at school in childrenâs with separation anxiety disorder. Token economy is a behavior treatment to reduce attachment behavior at school. The hypothesis was economy token could change attachment behavior at school with separation anxiety disorder aged 7 years. This research design was Single Case Experimental.Design with multiple-baseline design. In the research subjects was one child in elementary school with separation anxiety disorder. Data collected from monitoring sheet were analyzed with conservative-dual criteria(CDC). The form of subjectâs attachment figure behavior in school (1) looked into attachment figure to ensure the existence, (2) inquiring the material to his mother than his teacher at school, (3) inquiring to stay in front of the class and (4) closer to his mother than his friends when take arest. The result shows that therapy economy token can reduce attachment behavior at school in childrenâs with separation anxiety disorder. While the qualitative analysis shows there was parentsâ consistency in applying economy token program has played significant role in reducing attachment behavior at school in childrenâs with separation anxiety disorder.Keywords: attachment behavior at school in childrenâs, token economy therapy, separation anxiety disorder